What lies ahead - Apolinario, Basilio Miguel B., IX (Animo Repository, 2023)
What Lies Ahead is a short experimental animation that utilizes anecdotes from People Living with HIV (PLHIV) community members in the Philippines. The video is four (4) minutes and fifty-nine (59) seconds long and utilizes various art styles to create the video. The story begins with Antonio, an Overseas Filipino Worker (OFW) that comes back home from work. However, he secretly sleeps with men and cheats on Genevieve, a stay-at-home wife. After coming home and reuniting with his wife, they both figure out they have HIV after Antonio applies for a new job. Now, they struggle to adapt to their lives as Genevieve tries to cope with her husband’s affair and her pregnancy while Antonio rationalizes his sexuality and affection towards Genevieve. As a result of getting HIV, both harbor the stigma and physical problems associated with having the virus and the lives they must live moving forward. The thesis proponent made the short animation through the accounts of seven (7) PLHIV community members to give a realistic view of the story and experiences of the characters. The thesis proponent kept the interviewees’ identities confidential through pseudonyms, and the proponent ensured their responses through consent forms. Due to COVID-19, recording the voice actors and interviewees was conducted remotely in Zoom. The stylistics came from animations such as Midnight Gospel by Pendleton Ward and Minute Videos from YouTube. The component created the project through sketching, and illustrating in Adobe Photoshop, Illustrator, and Animate, then rendering in After Effects and Premiere Pro. 4K. MP4 Format.